Classification, impairments, and research inara table tennis: past, current, and future - Wu, S. K. (Sports and Health Sciences Notebooks, 2019)
Classification is the most important and complicated issue in disability sports. Currently, table tennis (TT) players with physical impairments (PI) and intellectual impairments (II) have been included at the Paralympic Games. There are ten classes for TT players with PI (five classes for wheelchair and five classes for standing players) and one class for players with II. TT-specific classification systems for PI players are physical and functional approaches and for II players are functional and cognitive approaches. 3S (speed, spin, and spot) principles are used to classify players with PI, and 3S and 3C (control, consistency, and change) principles are used to classify players with II. Para-TT classification systems are based on evidence and physical and functional evaluations. Medical and technical competent classifiers need to work together to make fair classifications for players. Recently, countries focused on winning medals at the major Championships and started to include elite able-bodied players with very mild impairments in Para-TT. The objective minimal impairment criteria (MIC) are urgently required by ITTF-PTT to maintain fairness of competition and protect actual disabled players. Therefore, evidence-based research is helpful to revise the TT classification system scientifically. In the presentation, the related evidence and information will be provided to identify and tackle the main issues and the future directions for Para-TT classification and research will be offered to include more scientists and classifiers.